'Minimalist approach' for transcatheter mitral valve replacement using intracardiac echocardiography and conscious sedation: a case series. Issue 3 (24th April 2020) - Cubeddu, Robert J; Sarkar, Abdullah; Navas, Viviana; Navia, Jose L
Abstract: Background: Transcatheter aortic valve implantation operators have adapted to a less invasive technique by foregoing the use of general anaesthesia and transoesophageal echocardiography. This is known as a 'minimalist approach'. This approach has yet to be explored in transcatheter mitral valve replacement (TMVR). Two patients with high perioperative risk underwent TMVR using only monitored conscious sedation (CS) and intracardiac echocardiography (ICE). Case summary: The patients were symptomatic and required treatment of severe mitral regurgitation and severe mitral stenosis in a mitral valve ring and prosthetic mitral valve, respectively. With the use of an antegrade transseptal approach, the procedure was conducted under CS using ICE only. After placement of the prosthetic mitral valve, the valve was assessed by advancing the ICE catheter through the interatrial septal defect and no significant paravalvular leak occurred. In one case, ad hoc treatment of right to left shunting was successfully pursued. Valve function was excellent immediately and at 24 h after implantation and resulted in significant haemodynamic improvement. Conclusion: With more TMVR cases being conducted, the 'minimalist approach' with CS and ICE may be considered in selected cases.